Variability of Grassland Soils’ Properties in Comparison to Soils of Other Ecosystems - Radoslava Kanianska; Miriam Kizeková (Agronomy)
The variety of natural conditions and land use patterns determine high variability of soil properties. This study focused on the analysis of chemical, physical, and biological properties of grassland (GL) soils (situated on slopes—GLS, and on alluvial plains—GLP) in comparison with soils of other ecosystems (arable land, forest land, riparian zone) in Central Slovakia. We applied an indicator’s method combined with models of these properties. The studies showed a large variability, more pronounced in GLS than in GLP. GLP soils were characterized by the highest number, biomass, and diversity of earthworms among all ecosystems. GL soils, in addition to FL soils, also have a relatively high capacity for water retention and C and N storage. However, we found an unfavorable state in available phosphorus, with GLS showing the lowest levels among compared ecosystems.